Core-shell structure C-coated Co / NF electrode material, preparation method and application thereof, and EC-C-coated Co / NF-PMS system

By growing a carbon-embedded cobalt core-shell structure in situ on a nickel foam substrate, a highly conductive and stable C@Co/NF electrode material is formed, which solves the problems of high energy consumption, low efficiency and poor stability of existing electrode materials when activating persulfate to degrade antibiotics, and achieves efficient and environmentally friendly pollutant degradation effect.

CN120922990AActive Publication Date: 2025-11-11JILIN NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511463041.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-11-11
Estimated Expiration
2045-10-14

AI Technical Summary

Technical Problem

Existing electrode materials suffer from high energy consumption, low efficiency, poor stability, high metal leaching rate, and insufficient environmental friendliness when activating persulfate to degrade antibiotics. Furthermore, traditional methods are difficult to achieve efficient, economical, and environmentally friendly pollutant degradation.

Method used

A core-shell structure C@Co/NF electrode material is used. By growing a carbon-encapsulated cobalt core-shell structure in situ on a nickel foam substrate and combining it with a nitrogen-doped carbon layer, a highly conductive and stable electrode material is formed, which is used to activate persulfate to degrade organic pollutants in water.

Benefits of technology

It achieves highly efficient electro-activated PMS, rapidly degrades SMX in water with a degradation rate of up to 95%, has good stability, almost no toxic release, low energy consumption, is suitable for the degradation of a variety of organic pollutants, and has a simple preparation process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120922990A_ABST
    Figure CN120922990A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sewage treatment, and relates to a core-shell structure C-coated Co / NF electrode material, a preparation method and application thereof, and an EC-coated Co / NF-PMS system.The electrode material takes foamed nickel as a three-dimensional conductive substrate, the core-shell structure of carbon-embedded cobalt elementary substance uniformly and compactly grows on the surface of the foamed nickel in situ, and four elements of C, O, Ni and Co are uniformly distributed in the C-coated Co / NF electrode material; wherein the atomic percentage content of carbon is the highest and exceeds 50%, the Co element is mainly Co0, two mixed valence states of Co < 3 + > and Co < 2 + > are introduced, the Ni element is mainly Ni < 2 + >, and meanwhile, the metallic nickel Ni0 of the substrate is reserved. The electrode material has high conductivity, high catalytic activity (excellent degradation capability), strong stability, good economical efficiency and environmental friendliness, and can be used for efficiently electrically activating PMS and deeply degrading organic pollutants such as SMX in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology and relates to the preparation of electrode materials for wastewater treatment. Specifically, it relates to a core-shell structure carbon-embedded cobalt (C@Co / NF) electrode material grown in situ on nickel foam (NF), its preparation method, and its application in degrading organic pollutants in wastewater. Background Technology

[0002] The residues of antibiotic pollutants in water bodies pose a serious threat to the ecological environment and human health. Sulfamethoxazole (SMX), a widely used antibiotic, is frequently detected in environmental water bodies. Traditional treatment methods, such as adsorption and biodegradation, suffer from problems such as low efficiency, easy secondary pollution, or incomplete degradation.

[0003] Currently, advanced oxidation techniques based on persulfate (SR-AOPs) are widely studied due to their strong oxidizing power. Their core lies in the efficient activation of PMS (permonosulfate) / PDS (perdisulfate) to generate sulfate radicals (SO4). ⁻ Traditional activation methods include heat, ultraviolet light, carbon materials, transition metal ions and their oxides, but these methods suffer from high energy consumption and secondary pollution. For example, homogeneous transition metal ions (such as Co) can cause these problems. 2+ While catalytic efficiency is high, it is prone to leaching, causing secondary pollution and is difficult to recycle. Electrocatalytic activation has become an emerging direction due to its strong controllability and environmental friendliness. Traditional electrode materials (such as Ti / PbO2) have drawbacks such as high energy consumption (>1.5V) when activating persulfate, low current efficiency (<50%), high dissolution rate of metal active components (>10%), and poor stability, resulting in low SMX degradation efficiency (<70%) and high operating costs.

[0004] Carbon-based materials derived from the pyrolysis of metal-organic frameworks (MOFs), such as zeolite imidazole ester framework material-67 / nickel foam composite material, ZIF-67 / NF, have been used in the field of electrocatalysis due to their high specific surface area and tunable electronic structure. However, the following problems still exist: (1) Precursor limitation: Conventional ZIF-67 (rhombic dodecahedron) pyrolysis easily generates CoO@C oxide cores, and the active sites of metallic cobalt are wrapped by the oxide layer, resulting in poor conductivity and insufficient active sites, and low electron conduction efficiency. (2) Poor structural stability: Powder catalysts require binder coating (such as polyvinylidene fluoride, PVDF), which leads to the masking of active sites and increased charge transport resistance. (3) Limited application scenarios: Existing research focuses on the energy field (such as lithium battery anodes and oxygen evolution reaction (OER) catalysis), and there are no reports on its use in the degradation of antibiotics in persulfate systems. Although recent studies have attempted to use ZIF (zeolite imidazolium ester framework)-derived materials for pollutant degradation (such as the degradation of florfenicol by cobalt-nitrogen co-doped carbon nanofibers Co-N / CNF), these studies employ an electrospinning composite process, which is cumbersome and makes it difficult to control the uniformity of the core-shell structure. Furthermore, cobalt in these materials is primarily composed of Co... 2+ / Co 3+ The presence of oxides results in insufficient conductivity, leading to limited activation efficiency of PMS (SMX degradation rate <70%). In addition, existing studies have explored using metal oxides (such as Co3O4) or carbon materials loaded on substrates (such as nickel foam NF) as electrocatalytic anodes for PMS activation, but they generally have one or more of the following problems: (1) Catalytic activity needs to be improved: The activation efficiency of many electrode materials for PMS is insufficient to achieve rapid degradation of pollutants, requiring a high overpotential. (2) Insufficient stability: During long-term electrochemical processes, especially in complex actual aquatic environments, active components (such as cobalt) are prone to dissolution or loss (e.g., >5%), leading to a decrease in catalytic activity and potentially causing secondary pollution. (3) Poor bonding between substrate and catalyst layer: The bonding between the active catalyst layer and the conductive substrate (such as NF) is not strong, and it is easy to peel off under long-term operation or hydraulic scouring, affecting the electrode life. (4) Preparation cost and economy: Although electrode materials relying on precious metals (such as Ir, Ru) may have better performance, their high cost limits their large-scale practical application. (5) Toxicity concerns: If the metal leaching amount is high during the catalytic process, its biotoxicity may have a negative impact on the environment, and its environmental friendliness needs to be improved.

[0005] In summary, there is an urgent need to develop an electrode material that combines high conductivity, high catalytic activity, excellent stability (low metal leaching), good economics, and environmental friendliness for the efficient electroactivation of PMS and the deep degradation of organic pollutants such as SMX in water. Summary of the Invention

[0006] In view of the shortcomings and deficiencies of the existing technology, the purpose of this invention is to provide a core-shell structure C@Co / NF electrode material that has high conductivity, high catalytic activity (excellent degradation ability), strong stability, good economy and environmental friendliness. This material can efficiently electroactivate PMS and deeply degrade organic pollutants such as SMX in water.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A core-shell structured C@Co / NF electrode material is described. The electrode material uses nickel foam as a three-dimensional conductive substrate, and a uniform and dense in-situ grown core-shell structure of carbon-embedded cobalt is grown on the surface of the nickel foam. The four elements C, O, Ni, and Co are uniformly distributed in the C@Co / NF electrode material, with carbon having the highest atomic percentage, exceeding 50%, and Co being the dominant element. 0 Mainly, and introduce Co 3+ With Co 2+ Two mixed valence states, Ni element as Ni 2+ Primarily based, while retaining the original metallic nickel (Ni) of the substrate. 0 .

[0008] This invention also provides a method for preparing a core-shell structured C@Co / NF electrode material, the method comprising the following steps: Step 1. Pretreatment of nickel foam: The purchased raw nickel foam was cut into appropriate sizes and ultrasonically treated with 1.0 M hydrochloric acid solution, deionized water, and anhydrous ethanol respectively. Finally, it was washed with deionized water and dried in a forced-air drying oven for later use. Step 2. Preparation of ZIF-L / NF: 2-Methylimidazole and Co(NO3)2·6H2O were dissolved separately in beakers containing deionized water, and the two solutions were stirred continuously until completely dissolved. Then, the dissolved Co(NO3)2·6H2O solution was poured into the dissolved 2-methylimidazole solution, and the pretreated nickel foam was fixed and suspended in the mixed solution. After that, the beaker was placed in a forced-air drying oven for static in-situ growth at room temperature. Finally, it was washed three times with deionized water until the solution became clear, and then dried in a forced-air drying oven to obtain the ZIF-L / NF precursor, namely the cobalt-based zeolite imidazole ester framework-leaf structure / nickel foam composite material. Step 3. Preparation of C@Co / NF: The ZIF-L / NF precursor prepared in step 2 is cut into a suitable size, then placed in the center of a crucible and placed in a tube furnace. First, N2 is introduced to isolate the air in the furnace, and then the temperature is raised to 500-600℃ in 30 minutes and heated for 100-150 minutes. After cooling to room temperature, it is taken out to obtain C@Co / NF electrode material, namely carbon-embedded cobalt-core-shell structure / foamed nickel composite material.

[0009] As a preferred embodiment of the present invention, the mass ratio of 2-methylimidazole to Co(NO3)2·6H2O in step 2 is 2-3:1. The pretreated nickel foam is fixed with paper clips and allowed to grow statically in situ at room temperature for 10-16 h. When drying in a forced-air drying oven, the temperature is controlled at 40-60℃ and the drying time is 4-8 h.

[0010] As a preferred embodiment of the present invention, after passing N2 through in step 3, the temperature is raised to 600°C within 30 minutes, and the heating time is continued for 120 minutes.

[0011] As a further preferred embodiment of the present invention, in step 2, the amount of 2-methylimidazole is 1300 mg, the amount of Co(NO3)2·6H2O is 582 mg, the growth is carried out statically in situ at room temperature for 12 h, and the drying is carried out in a forced-air drying oven at a controlled temperature of 60°C for 6 h.

[0012] The core-shell structured C@Co / NF electrode material provided by this invention has excellent activation ability for persulfate, and therefore it can be used as a persulfate activator in the activation of persulfate, wherein the persulfate is persulfate or perdisulfate.

[0013] In the degradation experiment of sulfamethoxazole, the core-shell structure C@Co / NF electrode material provided by this invention, in synergy with persulfate, can achieve a removal rate of 97.35% in 15 minutes; therefore, it can be applied to the degradation of organic pollutants in wastewater.

[0014] This invention also provides an EC-C@Co / NF-PMS system for electrocatalytic degradation of organic pollutants in wastewater. The system uses a core-shell structured C@Co / NF electrode material as the anode of the electrolytic cell and a carbon rod electrode as the cathode. The anode and cathode are connected to an electrochemical workstation. The electrolytic cell contains wastewater to be degraded. Persulfate and current are added to the wastewater for degradation. The persulfate is permonosulfate.

[0015] As a preferred embodiment of the present invention, the organic pollutants in the wastewater are dyes and / or antibiotics.

[0016] As a further preferred embodiment of the present invention, the dye is Rhodamine B or methylene blue, and the antibiotic is sulfamethoxazole, tetracycline hydrochloride, or oxytetracycline hydrochloride.

[0017] Advantages and beneficial effects of the present invention:

[0018] (1) The C@Co / NF material with a cobalt metal core (Co) provided by this invention 0 The synergistic effect among the carbon shell and NF substrate enhances its electrocatalytic performance. The NF substrate provides a three-dimensional conductive network, promotes electron transport, and gives the electrode self-supporting properties, eliminating the need for a binder coating. The carbon shell effectively prevents the aggregation and dissolution of cobalt nanoparticles, improving stability (low metal dissolution). In addition, nitrogen doping within the carbon shell can regulate the electronic structure of the carbon layer, providing more active sites and enhancing the activation ability of PMS.

[0019] (2) In the preparation of the precursor of the present invention, ZIF-L(Co) precursor is grown in situ at room temperature. The two-dimensional leaf structure of ZIF-L(Co) is used to replace the conventional ZIF-67 (three-dimensional rhombus). By utilizing its high specific surface area and directional growth characteristics, uniform coverage of NF surface (coverage rate >90%) is achieved. Then, in a reducing atmosphere (N2), the metal cobalt core (non-oxide) is generated by pyrolysis. The ZIF-L(Co) grown in situ is modified into a compact and dense carbon layer structure with core and shell structure, thereby forming a unique structure of nitrogen-doped carbon shell-coated metal cobalt nanoparticles (C@Co) on the NF surface, completely avoiding the problem of insufficient conductivity caused by the use of binders.

[0020] (3) In this invention, ZIF-L(Co) is grown in situ on NF and then pyrolyzed, so that the final C@Co is firmly bonded to the NF substrate and is not easy to fall off, ensuring long-term stability (90% of SMX can be removed within 30 minutes in five consecutive runs). Moreover, the toxicity of the material can be significantly reduced after the pyrolysis operation, greatly reducing the risk to the ecological environment.

[0021] (4) This invention is the first to use C@Co / NF as an electrocatalytic anode to activate the degradation of SMX by persulfate, which is achieved at 0.5 mA / cm 2 Under the conditions of current density, 0.54 mM PMS, and 10 mg / L SMX, the degradation rate of SMX is as high as 95% in 6 min, and the TOC removal rate is 68.2% within 30 min. It has the advantages of fast degradation speed, good degradation effect, and can degrade most SMX into non-toxic and harmless small molecules, making it safe and environmentally friendly.

[0022] (5) The electrode material itself and the degraded solution in the EC-C@Co / NF-PMS system provided by the present invention are almost non-toxic and have very low environmental harm, and will hardly cause any toxic harm to the environment.

[0023] (6) The power consumption of the EC-C@Co / NF-PMS system provided by this invention is 0.0042 kWh / m³. 3 The energy consumption is extremely low, indicating that the EC-C@Co / NF-PMS system has both high efficiency and low energy consumption in processing SMX, making it more economical and practical.

[0024] (7) The EC-C@Co / NF-PMS system provided by the present invention has a good degradation effect on common water pollutants such as dye organics and antibiotics. It can remove 99.83% of Rhodamine B (RhB) within 4 min, 95.10% of Methylene Blue (MBT) within 10 min, 96.45% of Oxytetracycline Hydrochloride (OTC) within 15 min, and 99.08% of Tetracycline Hydrochloride (TC) within 30 min. It can be seen that it has universal applicability in pollutant removal.

[0025] (8) The EC-C@Co / NF-PMS system provided by the present invention not only has good performance in the treatment of stationary phase SMX, but also has great potential in the treatment of mobile phase SMX. After 24 cycles, the performance activity remains greater than 70%, which provides a new solution for the efficient degradation of organic pollutants in mobile phase water.

[0026] (9) The process used to prepare the electrode material in this invention is simple and has a low cost. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the synthesis of the core-shell structured C@Co / NF material in this invention; where a is a schematic diagram of the synthesis process; and b is a schematic diagram of NF suspended vertically on a beaker. Figure 2 A comparison diagram of the C@Co / NF prepared in this invention with the ZIF-L / NF precursor and NF; Figure 3 These are morphological characterization diagrams of the present invention; wherein, (a) is the main synthetic route of C@Co / NF; (b1) is a SEM image of NF; (b2) is a SEM image of ZIF-L (Co) / NF; (c1-c2) are SEM images of C@Co / NF at 100μm and 50μm; (d1) is a TEM image of C@Co powder; (d2) is an HR-TEM image of C@Co powder; and (e) is an EDS mapping image of C@Co / NF. Figure 4 The following are the EDS energy spectra of each element in the C@Co / NF material of this invention; Figure 5 The diagram shows the structural characterization of the present invention; wherein, (a) is the XRD of NF, ZIF-L (Co) / NF, and C@Co / NF; (b) is the XRD of ZIF-L (Co) powder and C@Co powder; (c) is the XPS spectrum of C@Co / NF; (d) is the C element XPS of C@Co / NF; (e) is the O element XPS of C@Co / NF; (f) is the Co element XPS of C@Co / NF; and (g) is the Ni element XPS of C@Co / NF. Figure 6 This is a comparison chart of the degradation performance of the present invention; where (a) and (b) represent the degradation performance and first-order kinetic constant of SMX in different systems, respectively; experimental conditions: pH = 6.5 ± 0.2, [C@Co / NF] = 2 × 2 cm⁻¹ 2 EC = 0.5 mA / cm 2 [PMS] = 0.54 mM, [SMX] = 10 mg / L, V = 120 mL, [Na2SO4] = 50 mM, stirring speed = 150 rpm; Figure 7 This is a comparison of the mineralization rates of SMX within 30 min using the EC-C@Co / NF and EC-C@Co / NF-PMS synergistic systems of this invention; experimental conditions: pH = 6.5 ± 0.2, [C@Co / NF] = 2 × 2 cm⁻¹ 2 EC=0.5 mA / cm 2 [SMX] = 10 mg / L, [PMS] = 0.54 mM, V = 120 mL, [Na2SO4] = 50 mM, stirring speed = 150 rpm.

[0028] Figure 8 The images show a comparison of SEM images of the EC-ZIF-L / NF-PMS system before and after the ZIF-L / NF cycle; where (a1) and (a2) are before the ZIF-L / NF cycle; and (b1) and (b2) are after the ZIF-L / NF cycle. Figure 9 The effect of the EC-C@Co / NF-PMS system on the COD of SMX solution was investigated; (a) COD content before and after the SMX reaction; (b) COD removal rate after 30 min of reaction; experimental conditions: pH = 6.5 ± 0.2, [C@Co / NF] = 2 × 2 cm⁻¹ 2 EC=0.5 mA / cm 2,[SMX] = 10 mg / L,[PMS]= 0.54 mM,V=120 mL,[Na2SO4]=50 mM,Stirringspeed=150 rpm; Figure 10 This invention provides a stability assessment of C@Co / NF; wherein, (a) is a stability study of SMX degradation cycling; (b) is the XRD pattern before and after C@Co / NF cycling; (c) is the XRD pattern before and after C@Co (Power) cycling; (d) is the total XPS spectrum before and after C@Co / NF cycling; (e) is the Ni element XPS spectrum before and after C@Co / NF cycling; (f) is the Co element XPS spectrum before and after C@Co / NF cycling; (g) is the C element XPS spectrum before and after C@Co / NF cycling; (h) is the SEM image before C@Co / NF cycling; (i) is the SEM image after C@Co / NF cycling; and (j) is the EDS mapping image after C@Co / NF cycling. Figure 11 Images showing the growth status of NIH-3T3 cells under different concentrations of C@Co (Powder) and ZIF-L (Powder); where (a) is the growth status image under C@Co (Powder); and (b) is the growth status image under ZIF-L (Powder). Figure 12 The experiment was a CCK-8 staining experiment; (a) shows the survival rate of NIH-3T3 cells after co-culturing with different concentrations of C@Co (Powder) and ZIF-L (Powder) for 2 h; (b) shows the survival rate of NIH-3T3 cells after co-culturing with SMX degradation solutions at different times under different systems for 2 h. Figure 13 Fluorescent staining images of NIH-3T3 live / dead cells under different concentrations of C@Co (Powder) and ZIF-L (Powder); Figure 14 Fluorescence images of live / dead NIH-3T3 cells stained with SMX degradation solutions for EC-ZIF-L / NF-PMS and EC-C@Co / NF-PMS systems; Figure 15This invention provides an evaluation of the practical application of the EC-C@Co / NF-PMS system. (a) compares the energy consumption of the EC-C@Co / NF-PMS system with previously reported electrocatalytic degradation systems for SMX; (b) shows the degradation performance of flowing SMX over 240 min; (c) shows a waterfall plot of the peak area changes of the characteristic SMX peaks in liquid chromatography over 240 min; (d) is a schematic diagram of the EC-C@Co / NF-PMS system for degrading continuously flowing SMX; and (e) shows the performance of the EC-C@Co / NF-PMS system in degrading different water pollutants. Experimental conditions: pH = 6.5 ± 0.2, [C@Co / NF] = 2 × 2 cm⁻¹ 2 EC=0.5 mA / cm 2 Pump A (10 mg / L SMX + 50 mM Na2SO4), Pump B (0.54 mM PMS + 50 mM Na2SO4), Total flow rate: 12 mL / min, V = 120 mL. Detailed Implementation

[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand the technical solutions described herein, but this does not limit the present invention.

[0030] 1. Instruments and Materials In this invention, all reagents used in high-performance liquid chromatography (HPLC) are chromatographic grade, and all other chemical reagents are analytical grade. Nickel foam (NF) was purchased from Kunshan Shangte New Materials Co., Ltd.; high-purity graphite carbon rods were purchased from Tianjin Zhongnuo Carbon Co., Ltd.; 2-methylimidazole (C4H6N2, 98%), cobalt nitrate hexahydrate (Co(NO3)2•6H2O, 98%), and sulfamethoxazole (SMX, C 10 H 11 N3O3S, 98%, was purchased from Anhui Zesheng Technology Co., Ltd.; sodium sulfate (Na2SO4, AR, 99%) and rhodamine B (RhB, C) were also purchased. 28 H 31 ClN2O3, AR), Methylene Blue (MBT, C) 16 H 18 ClN3S, ≥98%, tetracycline (TC, C 22 H 24 N2O8), oxytetracycline hydrochloride (OTC, C2H) 24N2O9.HCl, 95% and phosphoric acid (H3PO4, AR, ≥85 wt%) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; raw nickel foam (NF, 99.99%) was purchased from Kunshan Shangte New Materials Co., Ltd.; hydrochloric acid (HCl, AR) was purchased from Chengdu Kelong Chemical Co., Ltd.; anhydrous ethanol (CH3CH2OH, ≥99.7%) was purchased from Chengdu Kelong Chemical Co., Ltd. Wt%) was purchased from Tianjin Tianli Chemical Reagent Co., Ltd.; persulfate (KHSO5 (≥42%)•0.5KHSO4•0.5K2SO4) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Calcein / PI Cell Viability and Cytotoxicity Assay Kit (C2015M) was purchased from Shanghai Beyotime Biotechnology Co., Ltd.; Nitric acid (HNO3, AR) was purchased from Sinopharm Chemical Reagent Co., Ltd.; 5,5-dimethyl-1-pyrrolidone N-oxide (DMPO) and 2,2,6,6-tetramethylpiperidine (TEMP) were purchased from Merck Biosciences GmbH, Germany; and high-purity graphite carbon rods were purchased from Tianjin Zhongnuo Carbon Co., Ltd.

[0031] The crystal structure was determined by Cu Kα radiation X-ray diffraction (XRD) on a D-MAX2500 (Rigaku, Japan); the morphology and elemental distribution were observed using scanning electron microscopy (SEM, Hitachi, Japan, 8100) and energy-dispersive X-ray spectroscopy (EDX, AZtec LiveUltimMax100); the microstructure and structure of the material were observed using transmission electron microscopy (TEM, Hitachi, Japan, HT-7800) and high-resolution transmission electron microscopy (HR-TEM, Thermo Fisher Scientific, USA, TG-G20); and X-ray photoelectron spectroscopy (XPS, Shimadzu, Japan, AXIS ULTRA) was used. DLD (Digital Degradation Lattice) was used to verify the elemental composition of the material; an electrochemical workstation (Shanghai Chenhua, CHI600E) was used for electrocatalytic experiments and electrochemical tests; intermediate products in the degradation solution were detected by liquid chromatography-mass spectrometry (LC-MS, Agilent Technologies, 1290II-6460); a multifunctional microplate reader (Tecan, Spark 30086376) was used to detect cell viability levels; and an inverted biological microscope (Leica, DM IL LED) was used. Fluo (11521265, 11521274) was used to observe and photograph cell growth; peristaltic pumps (Baoding Rongbai, BT100-2J, YZ1515) were used to realize solution flow dynamics; a digestion system (HACH, LTG082.03.40003, 14040C0126) was used for COD sample pretreatment; a spectrophotometer (Shanghai Instrument & Electronics, 071114050012) was used to detect the absorbance of COD sample; a TOC analyzer (Elementar, 38.00-5500, Inbetrieb-vario-TOC-D) was used to detect the total organic carbon content in the solution; and a UV-Vis spectrophotometer (Beijing Purkinje, TU-1810) and high-performance liquid chromatography (Beijing Dongxi Analysis, LC-5510) were used to detect the degree of degradation of pollutants in the solution.

[0032] 2. Methods and Results 2.1. Preparation of C@Co / NF: 2.1.1 NF Preprocessing Cut the purchased raw NF into pieces measuring 2×3.5 cm. 2 The samples were subjected to ultrasonic treatment with 1.0 M hydrochloric acid solution for 5 min, deionized water for 5 min, and anhydrous ethanol for 5 min, respectively. Finally, they were washed three times with deionized water and dried in a forced-air drying oven at 60 ℃ for 6 h for later use.

[0033] Preparation of ZIF-L (Co) in situ growth tools: Use pliers to shape paperclips into a "clothes hanger" and secure NF (2×3.5 cm) with paperclips.2 At the top center, insert the NF (non-flecked metal) secured with a paperclip into the "coat hanger," and use pliers to adjust the height of the paperclip to ensure that the NF is suspended vertically in the center of the 50 mL beaker. Figure 1 (b)

[0034] 2.1.2. Preparation of ZIF-L(Co) / NF 1300 mg of 2-methylimidazole (2-Melm) and 582 mg of Co(NO3)2·6H2O were dissolved separately in 50 mL beakers containing 25 mL of deionized water. Both solutions were stirred continuously for 5 min until completely dissolved. Then, the dissolved red Co(NO3)2·6H2O solution was slowly and gently poured into the dissolved colorless 2-methylimidazole solution. The mixed solution quickly turned light purple. After the mixed solution stood for 20 s, a pretreated (2 × 3.5 cm) solution was then poured into the beaker. 2 The NF precursor was slowly suspended in the mixed solution using a paperclip. Then, the beaker was placed in a forced-air drying oven and allowed to grow in situ at room temperature for 12 h. Finally, it was washed three times with deionized water until the solution became clear, and then dried at 60°C for 6 h in a forced-air drying oven to obtain the ZIF-L(Co) / NF precursor, namely a cobalt-based zeolite imidazole ester framework-leaf structure / nickel foam composite material.

[0035] 2.1.3. Preparation of C@Co / NF Prepared (2×3.5 cm) 2 ZIF-L(Co) / NF precursors were cut into (2×2 cm) pieces. 2 The sample was sized as follows: it was placed in the center of a rectangular crucible and then placed in a tube furnace. First, N2 was passed through the furnace for 30 minutes to isolate the air inside. Then, the temperature was raised to 600℃ for 30 minutes and heated for 120 minutes (holding for 2 hours). After cooling to room temperature, it was taken out to obtain C@Co / NF electrode material, namely carbon-embedded cobalt-core-shell structure / foamed nickel composite material. Figure 1 (a) is a schematic diagram of the specific synthesis process of C@Co / NF. Figure 2 Images show the appearance of successfully synthesized ZIF-L / NF and C@Co / NF, where NF is gray, ZIF-L / NF is light purple, and C@Co / NF is black. The materials grow uniformly and densely in situ on NF.

[0036] 2.2. Characterization and Testing:

[0037] 2.2.1. Morphological Characterization of C@Co / NF like Figure 3As shown in (a), a ZIF-L(Co) / NF precursor was successfully prepared on NF by room temperature deposition. Then, the ZIF-L(Co) / NF was calcined at 600℃ in a tube furnace under a N2 atmosphere to obtain C@Co / NF. The morphology of NF, ZIF-L(Co) / NF, and C@Co / NF materials was characterized using scanning electron microscopy. Figure 3 (b1) It can be seen that the original NF surface is relatively smooth, with no material on its surface. From Figure 3 (b2) It can be seen that after ZIF-L(Co) grows on NF, the smooth NF surface is composed of stacked, regularly leaf-shaped ZIF-L(Co) sheets. From Figure 3 As can be seen from (c1) and (c2), after calcination at 600℃ in a N2 atmosphere, the ZIF-L (Co) blade shape undergoes high-temperature pyrolysis and is derived into a core-shell structure composed of a layer of dense carbon material. It is speculated that this is because ZIF-L itself is modified into a core-shell structure of carbon-embedded cobalt at high temperature.

[0038] 2.2.2. Morphological and structural characterization To further verify the structure of C@Co / NF, C@Co powder scraped from C@Co / NF was subjected to transmission electron microscopy (TEM) and high-resolution TEM tests. The results are as follows: Figure 3 As shown in (d1) and (d2), the C@Co material exhibits a core-shell structure resembling carbon layers. High-resolution transmission electron microscopy (HRTEM) results are as follows: Figure 3 As shown in (d2), two distinct lattice fringes are clearly observable. The edge of the black area corresponds to the (002) crystal plane of graphitized carbon PDF#75-1621, with a lattice fringe spacing of 0.338 nm. The black area corresponds to the (111) crystal plane of PDF#89-7093, with a lattice fringe spacing of 0.202 nm. Furthermore, from... Figure 3 As shown in the energy-dispersive X-ray spectroscopy (EDS) of (e), all four elements (C, O, Ni, and Co) are present in the C@Co / NF material and are relatively uniformly distributed. The EDS spectra of each element in the C@Co / NF material are as follows: Figure 4 As shown, the atomic percentage of carbon is relatively high at 64.2%, indicating that C@Co / NF is mostly composed of carbon.

[0039] To further determine the structure of the materials, XRD patterns of NF, ZIF-L (Co) / NF, C@Co / NF, ZIF-L (Co) powder, and C@Co powder were tested, such as... Figure 5 As shown in (ab), from Figure 5(a) It can be seen that NF, ZIF-L (Co) / NF, and C@Co / NF have three diffraction peaks at 2θ = 45.10°, 52.44°, and 76.82°, which belong to the (111), (200), and (220) crystal planes of metallic Ni (PDF # 170-0989). Because the characteristic peaks of Ni are relatively high, they mask the characteristic peaks of ZIF-L (Co)-MOF and C@Co. To further verify the structure of the materials, ZIF-L (Co) powder and C@Co powder scraped from ZIF-L (Co) / NF and C@Co / NF were subjected to XRD tests, and the results are as follows: Figure 5 As shown in (b), the diffraction peaks of ZIF-L(Co) powder at 2θ = 7.2°, 10.3°, 10.9°, 12.7°, 15.0°, 17.0°, 18.0°, 22.0°, 23.0°, and 29.0° match the ZIF-L(Co) simulation standard card well, proving the synthesis of ZIF-L(Co) / NF material. In addition, the three diffraction peaks of C@Co powder at 2θ = 44.28°, 51.34°, and 76.7° belong to the (111), (200), and (220) crystal planes of metallic Co (PDF # 15-0806), while the diffraction peak near 2θ = 26.02° belongs to the (002) crystal plane of graphitized carbon (PDF # 75-1621). Based on previous transmission electron microscopy and high-resolution transmission electron microscopy results, it is confirmed that the C@Co / NF material has a core-shell structure of carbon-embedded cobalt.

[0040] Furthermore, this invention employs X-ray photoelectron spectroscopy (XPS) to investigate the fine chemical properties of each element in C@Co / NF. For example... Figure 5 As shown in (c), the XPS full spectrum indicates that C@Co / NF is mainly composed of four elements: Ni, Co, O, and C, located at 854.08 eV, 780.08 eV, 529.08 eV, and 285.08 eV, respectively. The high-resolution XPS spectrum of Co 2p constructed based on C@Co / NF is shown below. Figure 5 As shown in (f), it mainly consists of seven characteristic peaks, among which Co 0 The characteristic peaks located at 778.9 eV, and near 781.0 and 795.0 eV, belong to Co. 3+ 2p 3 / 2 and Co 3+ 2p 1 / 2 The characteristic peaks near 785.8 eV and 796.5 eV are attributed to Co. 2 + 2p 3 / 2 and Co 2+ 2p 1 / 2The satellite characteristic peaks are located near 784.5 eV and 798.2 eV. The XPS spectrum of Ni element in C@Co / NF is as follows... Figure 5 As shown in (g), the peaks at 855.8 eV and 874.0 eV are attributed to Ni, respectively. 2+ 2p 2 / 3 and Ni 2+ 2p 1 / 2 The two oscillation peaks (861.3 eV and 879.8 eV) are attributed to Ni 2p. 3 / 2 and Ni 2p 1 / 2 satellite peak, Ni 0 2p 3 / 2 and Ni 0 2p 1 / 2 The peaks are located near 853.9 eV and 871.5 eV, respectively, which should be a result of the NF substrate itself. XPS analysis shows that Co exists on the C@Co / NF surface, and Co is present in the form of Co. 0 Primarily, by introducing Co and Ni elements in mixed valence states, PMS undergoes a valence state change during activation, achieving highly efficient catalytic activation of PMS. The O 1s and C 1s spectra of C@Co / NF are as follows: Figure 5 (d) and Figure 5 As shown in (e), Figure 5 The characteristic peaks near 529.5 eV and 531.1 eV in (d) correspond to lattice oxygen and water adsorption, respectively; Figure 5 The characteristic peaks near 284.7 eV and 288.1 eV in (e) correspond to sp, respectively. 2 Hybridized CC and CO groups.

[0041] 2.2.3. Electrocatalytic activation of persulfate for the degradation of sulfamethoxazole The degradation experiment of SMX was conducted in a 150 mL cylindrical electrolytic cell, with a reaction solution volume of 120 mL. Before the degradation experiment, carbon rod electrodes and C@Co / NF (2×2 cm⁻¹) were prepared. 2 These electrodes, acting as the cathode and anode respectively, are connected to an electrochemical workstation (Shanghai Chenhua CHI600E), placed horizontally with a 3 cm gap between them. The effective area of ​​the anode electrode is 3.6 cm². 2A saturated calomel electrode was used as the reference electrode, placed 2 cm apart from both the cathode and anode. 50 mM Na₂SO₄ was dissolved in the reaction solution beforehand using a magnetic stirrer at 150 rpm. PMS and current were simultaneously added to the SMX solution to begin the degradation experiment. At set time intervals, 1 mL samples were taken using a syringe. Each sample was filtered through a 0.22 μm aqueous filter and added to a 100 μL methanol vial for quenching. The SMX concentration was then immediately quantitatively determined using a high-performance liquid chromatography (HPLC) system (Beijing Dongxi Analytical LC5510) at a detection wavelength of 270 nm, using a (60%:40%) acetonitrile:acetic acid (0.1%) mixture as the mobile phase, a total flow rate of 1.0 mL / min, a test temperature of 35 °C, and a sample volume of 10 μL. Equation 1 was used to calculate the degradation rate, and Equation 2 was used to calculate pseudo-first-order kinetics for modeling. In the cyclic experiment, after each cycle, the electrode was washed three times with deionized water, dried in a forced-air drying oven at 60°C for 6 hours, and then the next cyclic experiment was performed.

[0042] 2.2.4. Analytical Methods Formula for calculating pollutant removal rate (Equation 1): Degradation rate (%) = [1 - (C)] t / C0)]×100%; The pseudo-first-order dynamics calculation formula (Equation 2): ln(C) t / C0) = -K obs t; Electricity consumption calculation formula (Equation 3): EE / O=(P×t×1000) / [V×60×lg(C0 / C t )]; The energy required per order of magnitude (EE / O) is an effective parameter for evaluating the energy consumption of an electrochemical process. It is defined as the kilowatt-hours (kWh) of electrical energy required to reduce the initial pollutant concentration by one order of magnitude in 1 cubic meter of wastewater. In the above formula, C... t C0 represents the pollutant concentration (mg / L) at this reaction time, C0 represents the initial pollutant concentration (mg / L), and K represents the concentration at that time. obs denoted by σ, t represents the reaction time (min), and P and V represent the total current power (kW) and the volume of the reaction system (L), respectively.

[0043] In this embodiment, the chemical oxygen demand (COD) content in the measurement solution was determined using the traditional K2CrO7 oxidation method (HJ / T 399-2007). The absorbance of the sample at 620 nm was measured using a photometer, and then substituted into the COD standard curve: C COD (mg / L) = 2.485 × 10 -4 Calculate its concentration using X+0.109.

[0044] 2.2.5. Performance Evaluation To verify the superior degradation performance resulting from the synergistic effect of the EC-C@Co / NF-PMS system, degradation experiments of SMX decomposition in different systems were compared, such as... Figure 6 As shown in (a). Meanwhile, the degradation rate constant is fitted using the pseudo-first kinetic model (Equation 2), as follows: Figure 6 (b) As a result, in the PMS system alone, a removal rate of 15.56% was achieved within 15 minutes, but only 19.19% was achieved within 30 minutes. This is because PMS itself has weak oxidation capacity, and its degradation of SMX is almost negligible. In the C@Co / NF system alone, a removal rate of 18.68% was achieved within 15 minutes, but only 22.15% was achieved within 30 minutes, indicating that the C@Co / NF material has poor adsorption capacity for SMX. However, in the C@Co / NF-PMS synergistic system, a removal rate of 97.35% could be achieved within 15 minutes, indicating that the C@Co / NF electrode material has a good activation capacity for PMS. In the EC (electrochemical)-C@Co / NF system, a removal rate of 42.92% could be achieved within 30 minutes, which is an improvement of 20.77% compared to the C@Co / NF system alone, indicating that the current applied to the anode plays a certain role in the degradation of SMX. Under the EC-C@Co / NF-PMS system, a degradation rate of over 90% can be achieved within 6 minutes, and SMX is almost completely removed within 10 minutes. Compared to the C@Co / NF-PMS system, which only achieves a removal rate of 43.53% within 6 minutes, this represents an improvement of 51.47%, indicating that the addition of current generates more SO4. •- The presence of strong oxidizing free radicals such as OH• leads to a significant performance improvement. Compared to the EC-NF-PMS synergistic system, which only achieves a removal rate of 67.42% within 30 min, the former exhibits significantly better performance. In summary, the addition of current has a certain promoting effect on the degradation of SMX. Simultaneously, the performance of the EC-ZIF-L / NF-PMS system was also tested. It can be seen that it has a slightly slower reaction rate than the EC-C@Co / NF-PMS system. Furthermore, the good performance of the former is due to MOF collapse, which leads to environmental risks, while the latter provides stable catalysis with extremely low environmental risks. Compared to other control systems, the EC-C@Co / NF-PMS synergistic system has a relatively high pseudo-first-order kinetic reaction rate constant.

[0045] This invention also compares the previously reported PS / PMS degradation SMX system to illustrate its excellent degradation performance from another perspective, as detailed in Table 1.

[0046] Table 1. Comparison of SMX degradation performance of different activated persulfate systems system PMS consumption SMX concentration Removal rate Time (min) EC-C@Fe / NF(II) 0.65 mM 25 mg / L 100% 30 EC-CC 1.00 mM 10 μM 80% 30 <![CDATA[Fe 0 @Fe3O4-MC]]> 0.80 mM 0.04 mM 100% 120 EC-BDD 1.00 mM 5 μM 84.67% 30 Zn-N@C 0.50 mM 25 μM 95.7% 20 CoFe / ZSM-5 0.6 g / L 10 mg / L 93% 60 EC-C@Co / NF (This invention) 0.54 mM 10 mg / L 95% 6 As can be seen from Table 1, the present invention has a fast degradation rate and good degradation effect. Under experimental conditions of low PMS consumption and high concentration of SMX, it has shown excellent removal effect. While removing SMX, it is beneficial to significantly reduce application costs and environmental hazards.

[0047] Furthermore, this invention also determined the mineralization rate of 10 mg / L SMX within 30 min in the EC-C@Co / NF and EC-C@Co / NF-PMS synergistic systems, and the results are as follows: Figure 7 As shown, through Figure 7 It can be seen that the EC-C@Co / NF-PMS synergistic system achieved a mineralization rate of 68.2% for 10 mg / L SMX within 30 min, significantly better than EC-C@Co / NF. This indicates that the system can degrade most SMX into non-toxic and harmless small molecules (CO2 and H2O), which is more environmentally friendly. Simultaneously, this invention also measured the total organic carbon in the EC-ZIF-L / NF-PMS system. It was found that after 30 min of reaction, the total organic carbon content of the solution doubled. This may be due to the leaching of the catalyst from the ZIF-L / NF onto the solution, indicating the electrocatalytic degradation and instability of the MOF itself. The results are as follows... Figure 8 As shown.

[0048] To further investigate the reactivity of SMX and its intermediates, the COD of the SMX solution was determined and calculated using the potassium dichromate oxidation method (HJ / T399-2007) in the EC-C@Co / NF-PMS system. The COD removal rate of SMX within 30 min was 76.88% (see...). Figure 9 This indicates that a large amount of SMX and byproducts were destroyed, resulting in a significant oxidation effect on reducing organic matter in water.

[0049] 2.2.6. Stability Assessment The reusability of C@Co / NF was evaluated. For example... Figure 10 As shown in (a), the EC-C@Co / NF-PMS system maintained a 90% SMX removal rate within 30 minutes during five consecutive runs, demonstrating good cycle stability. The SEM images after catalysis show (…). Figure 8 ZIF-L has almost completely detached from NF, which fully demonstrates the instability of ZIF-L / NF. Furthermore, this invention also tested XRD, SEM, and EDS-Mapping before and after using C@Co / NF, with results as follows... Figure 10As shown in (b), (h)-(j), the corresponding peaks on the catalyst-treated and untreated peaks correspond one-to-one. No significant changes were observed in the SEM images before and after catalyst treatment, and the EDS-Mapping after treatment indicated a uniform distribution of elements after catalysis. In addition, XPS values ​​of C@Co / NF were measured before and after catalysis. No significant changes were observed in the C@Co / NF survey and C 1s values ​​before and after catalyst treatment, as shown in (b), (h), and (j). Figure 10 As shown in (d)-(g). Due to the contact between C@Co / NF and the solution during the catalytic process, O... ads The proportion has increased. From Figure 10 As can be seen from (d)-(g), the proportions of some valence states of the metals in the Co 2p and Mn 2p spectra have changed to some extent. This is due to the metal-activated PMS catalytic process. In summary, the above results indicate that C@Co / NF possesses the structural stability required for the catalytic reaction.

[0050] 2.2.7. Cytotoxicity assay methods First, a culture medium containing 1% penicillin-streptomycin solution (HyClone), 10% fetal bovine serum, and 89% liquid medium (DMEM) was prepared. NIH3T3 cells (purchased from Beijing Huake Cell Biotechnology) were then added to the medium and cultured at 37 °C. The cell culture medium was changed daily. Once the NIH3T3 cells entered the logarithmic growth phase, NIH3T3 cells (5 × 10⁴ cells / mL) were added to 96-well plates containing 100 μL of DMEM and cultured for 24 h, with two replicates per well. After cell attachment, the supernatant was discarded, and 100 μL of catalyst or reaction solution (Blank, 0 min, 10 min, 30 min) at concentrations of 100 μg / mL, 200 μg / mL, 500 μg / mL, and 1000 μg / mL were added to each well. During culture, live and dead cells were stained with Calcein / PI, and cell growth was recorded using an inverted biological microscope. After co-culturing for 24 h, 10 μL of CCK-8 solution was added to each well, and after incubation for 4 h, the absorbance at 450 nm was measured using a microplate reader.

[0051] In the CCK-8 reagent, WST-8 is reduced to a yellow formazan product by dehydrogenases in the mitochondria of cells. The reduction is directly proportional to the cell number, and its absorbance at 450 nm using a microplate reader reflects the cell number. The cytotoxicity of different concentrations of the catalyst C@Co (100 μg / mL, 200 μg / mL, 500 μg / mL, and 1000 μg / mL) and reaction solutions (Blank, 0 min, 10 min, and 30 min) on NIH3T3 cells was assessed using CCK-8.

[0052] 2.2.8. Toxicity Assessment To further investigate the toxicity levels of the degraded SMX solution and the material itself to the environment, an NIH-3T3 cell compatibility assay was performed (see...). Figure 11 Cell counting kit-8 (CCK-8) experiment ( Figure 12 ) and live / dead / cell fluorescence staining assay ( Figure 13 Three methods are used to assess toxicity. Figure 11 Images show the natural growth of NIH-3T3 cells and their growth status under different concentrations of C@Co (Powder) and ZIF-L (Powder) materials. It can be seen that the cells initially adhered to the substrate. As the material concentration increased from 100 μg / mL to 1000 μg / mL, some cells gradually died due to the toxicity of the material, becoming floated and no longer adhering to the substrate. Figure 11 It is evident that as the material concentration increases, the number of NIH-3T3 cells exhibiting apoptosis under ZIF-L (Powder) is significantly greater than that under C@Co (Powder). This indicates that the modified C@Co (Powder) is far less toxic than ZIF-L (Powder). To more clearly demonstrate the degree of toxicity, this invention observed the toxicity levels of the two materials using live / dead cell staining fluorescence images (see...). Figure 13 Using Calcein, PI, and Calcein+PI dyes to specifically stain live cells (green), dead cells (red), and live (dead) cells, it can be seen that as the concentrations of ZIF-L (Powder) and C@Co (Powder) increase, the amount of red fluorescence gradually increases, indicating that the number of dead cells gradually increases. However, the number of cells killed by C@Co (Powder) is much lower than that caused by ZIF-L (Powder), indicating that the toxicity of C@Co (Powder) is much lower than that of ZIF-L (Powder). At a concentration of 100 ug / L, C@Co (Powder) can only cause the death of a few cells, and the catalyst concentration in the EC-C@Co / NF-PMS system is much lower than 100 ug / L, so it poses almost no toxicity to the environment.

[0053] To quantitatively assess the toxicity level, this invention also performed a CCK-8 staining experiment to quantitatively detect the number of viable cells after co-culturing with different concentrations of ZIF-L (Powder) and C@Co (Powder). The results are as follows: Figure 12As shown in (a), it can be seen that, compared with ZIF-L (Powder), the modified C@Co (Powder) has a very high cell survival rate, indicating that the latter has very low toxicity and will hardly cause any harm to the environment.

[0054] In addition to investigating the intrinsic toxicity of the materials, this invention also studied the toxicity levels of SMX degradation solutions at different time points in the EC-ZIF-L / NF-PMS and EC-C@Co / NF-PMS systems. Live (dead) cell staining images ( Figure 14 As can be seen, the Blank group (50 mM Na2SO4 aqueous solution) resulted in a small number of cell deaths, possibly due to the high salt concentration causing cell dehydration and apoptosis through osmosis. The 0 min group (10 mg / L SMX solution) showed a large number of NIH-3T3 cell deaths, indicating that the initial concentration of SMX solution had high toxicity. It can be seen that with the extension of degradation time, the EC-ZIF-L / NF-PMS and EC-C@Co / NF-PMS systems showed lower cell death fluorescence points in the 30 min group compared to the 10 min group, indicating a gradual decrease in toxicity. However, the EC-ZIF-L / NF-PMS system still caused a large number of cell deaths in the 30 min group, and compared to the 10 min group, there was no significant decrease in the fluorescence points of dead cells, and the situation was almost similar to that of the Blank group, indicating that it still has significant toxicity. In contrast, the EC-C@Co / NF-PMS system showed a significant reduction in the number of fluorescent dead cells in the 10-min group compared to the Blank group. Furthermore, as the degradation experiment progressed, the 30-min group showed almost no fluorescent dead cells, indicating that the solution had virtually no toxicity, and was lower than that of the Blank group. This may be because the EC-C@Co / NF-PMS system consumed some Na2SO4 while removing SMX, resulting in a lower salt concentration and reduced cell damage.

[0055] To quantitatively assess the toxicity levels of the solutions, the CCK-8 staining assay was used to determine the changes in the number of viable cells after co-culturing in various solutions for 2 hours. Figure 12 As shown in (b), it can be seen that the EC-C@Co / NF-PMS system has a higher overall cell survival rate after degradation than the EC-ZIF-L / NF-PMS system, and the cell survival rate of the 30-minute group reaches about 90% (higher than the Blank group). The above results fully demonstrate that the solution after degradation of the EC-C@Co / NF-PMS system is almost non-toxic and has extremely low environmental harm; it also indirectly shows the success of C@Co / NF modification.

[0056] 2.2.9. Assessment of Practical Application Potential To further verify the feasibility of the EC-C@Co / NF-PMS system in practical applications, this invention compares the energy consumption of this system with some previously reported electrocatalytic degradation of SMX. The energy consumption is calculated using Equation 3, and the results are as follows: Figure 15 As shown in (a), the power consumption of the EC-C@Co / NF-PMS system is 0.0042 kWh / m³. 3 The energy consumption is extremely low, which indicates that the EC-C@Co / NF-PMS system has high efficiency in processing SMX while still having low energy consumption.

[0057] Considering the diverse types of pollutants found in wastewater from natural environments, to further verify the degradation efficacy of the EC-C@Co / NF-PMS system for different types of pollutants, stationary phase degradation experiments were conducted on two common dyes (Rhodamine B (RhB) and Methylene Blue (MBT)) and two antibiotics (Tetracycline Hydrochloride (TC) and Oxytetracycline Hydrochloride (OTC)). Figure 15 As shown in (e), 99.83% of Rhodamine B (RhB) can be removed within 4 min, and 95.10% of Methylene Blue (MBT) can be removed within 10 min, indicating that this system can efficiently degrade dye-based organic compounds. However, 96.45% of Oxytetracycline Hydrochloride (OTC) can be removed within 15 min, and 99.08% of Tetracycline Hydrochloride (TC) can be removed within 30 min. The difference in removal efficiency for different pollutants and degradation efficiency for different antibiotics reflects the differences in the structure and activity of the pollutants, which also indirectly indicates the main active species of this system. 1 The catalytic selectivity of O2 plays a significant role in the catalytic process. Overall, the EC-C@Co / NF-PMS system demonstrates excellent performance for common water pollutants, indicating its broad applicability in pollutant removal.

[0058] To further simulate real-world wastewater treatment scenarios, this invention independently designed an electrocatalytic EC-C@Co / NF-PMS system for degrading continuously flowing SMX, such as... Figure 15 As shown in (d), an electrolyte aqueous solution containing 10 mg / L SMX + 50 mM Na2SO4 is used as the inlet water source A for pump A, and an electrolyte aqueous solution containing 0.54 mM PMS + 50 mM Na2SO4 is used as the inlet water source B for pump B. The two inlets of the inlet pipeline are inserted into inlet water source A and inlet water source B, respectively, and the outlet is connected to the inlet connector at the bottom of the cylindrical electrolytic cell. By controlling pumps A and B, the electrolyte aqueous solutions from inlet water source A and inlet water source B are delivered to the electrolytic cell. The electrolytic cell is set on the operating table, the reaction solution volume is 120 mL, and carbon rod electrodes and C@Co / NF (2×2cm) are used.2 These electrodes, acting as the cathode and anode respectively, are connected to the electrochemical workstation, placed horizontally with a 3 cm gap between them. The effective area of ​​the anode electrode is 3.6 cm². 2 A saturated calomel electrode was used as the reference electrode and placed at a 2 cm distance from the cathode and anode, respectively. A water outlet connector was provided at the top of the electrolytic cell, which was connected to the collection tank through the liquid outlet pipe. The flow rates of the two pumps were controlled to be the same, with a total flow rate of 12 mL / min. After 10 minutes, the mixed solution was just filled to the water outlet connector without overflowing. At this point, the current was started and continuously applied, and the solution was processed by the EC-C@Co / NF-PMS system. The time was recorded when the solution overflowed from the water outlet connector. After that, water was taken from the water outlet connector every 10 minutes for further detection of SMX content. Figure 15 (b) SMX under continuous degradation in a flowing state for 240 min. The results show that the EC-C@Co / NF-PMS system can remove more than 70% of SMX within 10 min, and can still maintain a removal rate of more than 70% within 240 min as the number of consecutive treatments increases. Figure 15 (c) is a schematic diagram of the peak area changes in SMX liquid chromatography. These results indicate that the EC-C@Co / NF-PMS system not only performs well in processing stationary phase SMX, but also shows great potential in processing mobile phase SMX.

[0059] The above-described specific examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various simple deductions, modifications, or substitutions based on the principles of this invention. Therefore, the scope of protection of this invention should be determined by the scope of the claims.

Claims

1. A core-shell structured C@Co / NF electrode material, characterized in that, The electrode material uses nickel foam as a three-dimensional conductive substrate. A uniform and dense core-shell structure of carbon-embedded cobalt is grown in situ on the surface of the nickel foam. The four elements C, O, Ni, and Co are uniformly distributed in the C@Co / NF electrode material, with carbon having the highest atomic percentage, exceeding 50%, and Co being the dominant element. 0 Mainly, and introduce Co 3+ With Co 2+ Two mixed valence states, Ni element as Ni 2+ Mainly, while retaining the metallic nickel (Ni) of the substrate itself. 0 .

2. A method for preparing a core-shell structured C@Co / NF electrode material, characterized in that, The method includes the following steps: Step 1. Pretreatment of nickel foam: The purchased raw nickel foam was cut into appropriate sizes and ultrasonically treated with 1.0 M hydrochloric acid solution, deionized water, and anhydrous ethanol respectively. Finally, it was washed with deionized water and dried in a forced-air drying oven for later use. Step 2. Preparation of ZIF-L / NF: 2-Methylimidazole and Co(NO3)2·6H2O were dissolved separately in beakers containing deionized water, and the two solutions were stirred continuously until completely dissolved. Then, the dissolved Co(NO3)2·6H2O solution was poured into the dissolved 2-methylimidazole solution, and the pretreated nickel foam was fixed and suspended in the mixed solution. After that, the beaker was placed in a forced-air drying oven for static in-situ growth at room temperature. Finally, it was washed three times with deionized water until the solution became clear, and then dried in a forced-air drying oven to obtain the ZIF-L / NF precursor, namely the cobalt-based zeolite imidazole framework-leaf structure / nickel foam composite material. Step 3. Preparation of C@Co / NF: The ZIF-L / NF precursor prepared in step 2 is cut into a suitable size, then placed in the center of a crucible and placed in a tube furnace. First, N2 is introduced to isolate the air in the furnace, and then the temperature is raised to 500-600℃ in 30 minutes and heated for 100-150 minutes. After cooling to room temperature, it is taken out to obtain C@Co / NF electrode material, namely carbon-embedded cobalt-core-shell structure / foamed nickel composite material.

3. The method for preparing a core-shell structured C@Co / NF electrode material according to claim 2, characterized in that, In step 2, the mass ratio of 2-methylimidazole to Co(NO3)2·6H2O is 2-3:

1. The pretreated nickel foam is fixed with paper clips and allowed to grow statically in situ at room temperature for 10-16 h. When drying in a forced-air drying oven, the temperature is controlled at 40-60℃ and the drying time is 4-8 h.

4. The method for preparing a core-shell structured C@Co / NF electrode material according to claim 2, characterized in that, After passing N2 through in step 3, the temperature is raised to 600℃ in 30 minutes and the heating time is continued for 120 minutes.

5. The method for preparing a core-shell structured C@Co / NF electrode material according to claim 3, characterized in that, In step 2, the amount of 2-methylimidazole used was 1300 mg, and the amount of Co(NO3)2·6H2O used was 582 mg. The plant was allowed to grow statically in situ at room temperature for 12 h, and then dried in a forced-air drying oven at a controlled temperature of 60℃ for 6 h.

6. The C@Co / NF electrode material prepared by the method according to any one of claims 2 to 5 is used as a persulfate activator in the activation of persulfate, wherein the persulfate is permonosulfate or perdisulfate.

7. The C@Co / NF electrode material prepared by the method according to any one of claims 2 to 5 is used in the degradation of organic pollutants in wastewater.

8. An EC-C@Co / NF-PMS system for electrocatalytic degradation of organic pollutants in wastewater, characterized in that, The system uses C@Co / NF electrode material prepared by any one of claims 2 to 5 as the anode of the electrolytic cell and carbon rod electrode as the cathode of the electrolytic cell. The anode and cathode are connected to an electrochemical workstation. The electrolytic cell contains wastewater to be degraded. Persulfate and current are added to the wastewater for degradation. The persulfate is permonosulfate.

9. The EC-C@Co / NF-PMS system for electrocatalytic degradation of organic pollutants in wastewater according to claim 8, characterized in that, The organic pollutants in the wastewater are dyes and / or antibiotics.

10. The EC-C@Co / NF-PMS system for electrocatalytic degradation of organic pollutants in wastewater according to claim 9, characterized in that, The dye is Rhodamine B or methylene blue, and the antibiotic is sulfamethoxazole, tetracycline hydrochloride, or oxytetracycline hydrochloride.

Citation Information

Patent Citations

  • Core-shell structure composite material composed of transition metal oxide grown on nickel foam in situ and metal organic skeleton

    CN109659150A

  • Foamed nickel loaded carbon embedded zero-valent iron cathode, preparation method and antibiotic degradation method

    CN114560538A

  • Catalyst, system and method for mineralization of organic pollutants

    US20250303398A1

  • KR20250049469A